Prognostic Immune-Related Genes of Patients With Ewing’s Sarcoma - Zhou, Yangfan; Xu, Bin; Wu, Shusheng; Liu, Yulian (Frontiers in Genetics, 2021)
Ewing’s sarcoma (ES) is an extremely aggressive malignant bone tumor with a high incidence among children and adolescents. The immune microenvironment plays an important role in ES development. The aim of the current study was to investigate the immune microenvironment in ES patients to identify immune-related gene signatures. Single-sample gene set enrichment analysis (ssGSEA) was used to cluster the RNA sequences of 117 ES patients, and their immune cell infiltration data were downloaded and evaluated based on the Gene Expression Omnibus (GEO) database. High, medium, and low immune cell infiltration clusters were identified. Based on the comparison of clusters with high and low immune cell infiltration, normal skeletal muscle cells, and ES, we identified 198 common differentially expressed genes. GO and KEGG enrichment analyses indicated the underlying immune mechanism in ES. Cox and LASSO regression analyses were conducted to select immune-related prognostic genes. An external dataset from the International Cancer Genome Consortium (ICGC) was used to validate our results. Ten immune-related, independent prognostic genes (FMO2, GLCE, GPR64, IGFBP4, LOXHD1, PBK, SNAI2, SPP1, TAPT1-AS1, and ZIC2) were selected for analysis. These 10 immune-related genes signature were determined to exhibit independent prognostic significance for ES. The results of this study provide an approach for predicting the prognosis and survival of ES patients, and the elucidated genes may be a promising target for immunotherapy.